KABA AND NOVEL AND MINANGKABAU SOCIETY : HISTORY OF IDEAS' - Umar Junus (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2000)
It is assumed that a folktale is what we inherit from the past, narrating a remote or an a-historical past event . However, a kaba, a traditional Minang(kabau) storytelling 2. which is generally and generically classified as a folktale 3 . shows a different picture. Some kabas might be inherited from the past as they are available in manuscript form and/or are supposed to be recorded from an oral tradition, relating an event in a-historical past narrated by an anonymous storyteller. However, there are also kabas with different character. They are neither inherited from the past nor recorded from the traditional oral tradition . Some appeared, for the first time, in printed form while others were commercially published in audio-cassette - a new kind of orally transmitted storytelling, benefiting the introduction of the new technologies, the printing since 1920s and the audio since 70s - flourishing since 70s - respectively . Although some kabas in printed or audiocassette form might relate events supposed to take place in a remote past, re-narrating the story of old kabas, however most of them are relating contemporary or immediate past events . They are no longer author-less as authors' names - in kabas in audio-cassette it is replaced by the name of the storyteller - are printed on the cover of the printed kabas or on the label of audio cassettes . Although a kaba - its form resembles that of a pantun - is formally and stylistically a traditional literature . supposed to be inherited from the oral tradition - it is per- * Pakar Sastra . pernah menjadi guru besar di Universitas Malaya . Humaniora Volume Xll. No . 2/2000 petuated by kabas published in cassette form after an intermezzo with kabas in printed form - it however has an ability to express new ideas, relating either the contemporary or the past events . It is then proper to treat it, its history and its